Value at Risk and Markowitz Portfolio Optimization in Agricultural Sector Stocks - Vicka Pramudya Putra; Roni Afrizal; Arnayulis Arnayulis; Azzukhruf Ariliusra (Journal of Agriculture, 2026)
This study examines market risk in agricultural sector stocks listed on the Indonesia Stock Exchange (IDX) using the Value at Risk (VaR) approach based on historical simulation, both at the individual stock level and at the portfolio level. The data employed consist of daily closing price time series from January 2025 to December 2025, covering AALI, NSSS, TAPG, and SMAR. The estimation of portfolio VaR was preceded by the calculation of returns, expected returns, variances, standard deviations, and the variance–covariance matrix, which were subsequently utilized to construct the optimal portfolio under the Markowitz mean–variance framework. VaR was then measured at confidence levels of 90%, 95%, and 99%, assuming an initial investment value of IDR 1,000,000. The findings indicate that individual stock VaR increases as the confidence level rises, suggesting the presence of tail risk in the return distribution over the observation period. TAPG and NSSS consistently exhibit the highest VaR values, whereas AALI demonstrates relatively lower risk at the 90% and 95% confidence levels. The optimal portfolio comprises NSSS (59.49%), TAPG (28.27%), and SMAR (12.24%), yielding an expected portfolio return of 0.43% and a risk level (standard deviation) of 0.01899. The portfolio VaR is lower than that of the highest-risk individual stocks across the 90% and 95% confidence levels, underscoring the role of diversification and optimal weighting in mitigating downside risk.